Zambian Protestant Ecumenism and the Quest for Eco-Justice: A Case Study of the Council of Churches in Zambia - Sakupapa, Teddy (Scriptura, 2023)
This paper maps the trajectory of eco-justice discourse in Zambia with specific reference to the Council of Churches in Zambia (CCZ) as one of the most significant ecumenical structures in the country. Foregrounding the notion of eco-justice, this paper seeks to answer the question, namely, in what ways do religious resources (read: institutions) engender ecological ethos? Such a question is explored in light of the widely recognised inextricable link between environmental degradation and justice as expressed in the concept of eco-justice. Therefore, through documentary analysis, the paper delineates the theological basis of CCZ’s advocacy for eco-justice and underscores the potential of ecumenical institutions as sources of religious social capital. While underlining the role of religious resources in shaping people’s attitudes and behaviour towards the environment, the paper offers a critique of ‘prophetic voice’ by drawing attention to the need for clarity on the distinctive contribution of Christian resources in addressing ecological degradation.